The Effects of Exam Setting on Students’ Test-Taking Behaviors and Performances: Proctored Versus Unproctored - Yıldırım, Denizer; Ilgaz, Hale; Bayazıt, Alper; Akçapınar, Gökhan (International Review of Research in Open and Distributed Learning, 2023)
One of the biggest challenges for online learning is upholding academic integrity in online assessments. In particular, institutions and faculties attach importance to exam security and academic dishonesty in the online learning process. The aim of this study was to compare the test-taking behaviors and academic achievements of students in proctored and unproctored online exam environments. The log records of students in proctored and unproctored online exam environments were compared using visualization and log analysis methods. The results showed that while a significant difference was found between time spent on the first question on the exam, total time spent on the exam, and the mean and median times spent on each question, there was no significant difference between the exam scores of students in proctored and unproctored groups. In other words, it has been observed that reliable exams can be conducted without the need for proctoring through an appropriate assessment design (e.g., using multiple low-stake formative exams instead of a single high-stake summative exam). The results will guide instructors in designing assessments for their online courses. It is also expected to help researchers in how exam logs can be analyzed and in extracting insights regarding students' exam-taking behaviors from the logs.